Naringin content in local citrus fruits - Yusof, Salmah; Mohd Ghazali, Hasanah; King, Gan Swee (Elsevier Science Publishers, 1990)
The content of bitter component (naringin) from the skin, juice and seed of musk lime, mexican lime, rough lime, pummelo and mandarin orange was determined by the high-performance liquid chromatographic (HPLC) method. Naringin could only be found in pummelo and rough lime but could not be detected in musk lime, mexican lime and mandarin orange. The skin of pummelo contained a higher amount of naringin (3910 μg/g fresh weight) than the juice (220·0 μg/g fresh weight) whereas the amounts of naringin obtained from the skin, juice and seed of rough lime were 517·2 μg/g, 98·4 μg/g and 29·2 μg/g fresh weight, respectively. Sensory analysis further confirmed that the juices extracted from pummelo and rough lime were bitter while those extracted from musk lime, mexican lime and mandarin orange were not bitter. The correlation coefficient (r) for bitterness using both techniques (sensory and HPLC) was 0·97.